INFLUENCE OF COMPETENCE, ORGANIZATIONAL CULTURE, AND COMMITMENT ON EMPLOYEE PERFORMANCE AT PT. PLN (PERSERO) UIP3B SUMATERA UPT PALEMBANG - Sahri, Syaiful; Putri, Dita Marisa; Syahyuni, Syahyuni (ECOBISMA (JURNAL EKONOMI, BISNIS DAN MANAJEMEN), 2022)
This study discusses the Effect of Competence (X1), Organizational Culture (X2) and Commitment (X3) on Employee Performance (Y) which aims to examine the effect of Competence, Organizational Culture and Commitment on Employee Performance at PT. PLN (Persero) UIP3B UPT Sumatera Palembang. The sample used in this study was 55 employees with the saturated sample method. The information used is groundwork information and secondary information. Collecting information using a questionnaire and hypothesis testing using multiple regression analysis using the SPSS 24.0 program. The results of this test state that Competence, Organizational Culture, and Commitment have a positive and significant effect on employee performance. From the research conducted, the authors conclude that Competence, Organizational Culture, and Commitment have a positive direction coefficient on Employee Performance, Competency Correlation Coefficient, Organizational Culture, Commitment with Positive Correlation. Based on the t-test Competence (X1) has a significant effect on employee performance (Y) at PT. PLN (Persero) UIP3B Sumatra. Where tilapia X1 is 3.780 with a significance of 0.000 <0.05, while based on the t-test of Organizational Culture (X2) has a significant effect on employee performance (Y) at PT. PLN (Persero) UIP3B Sumatra. Where the t-count X1 is 5.228 with a significance of 0.000 <0.05, and based on the t-test commitment (X3) has a significant effect on employee performance (Y) at PT. PLN (Persero) UIP3B Sumatra. Where tilapia X1 is 3.780 with a significance of 0.015 <0.05.